Multipath and Multiparticle Tests of Complex versus Hypercomplex Quantum Theory - Saruhan, Ece İpek and von Zanthier, Joachim and Pleinert, Marc-Oliver (Physical Review Letters, 2025)
The axioms of quantum mechanics provide limited information regarding the structure of the Hilbert space, such as the underlying number system. The latter is generally regarded as complex, but generalizations of complex numbers, so-called hypercomplex numbers, cannot be ruled out in theory. Therefore, specialized experiments to test for hypercomplex quantum mechanics are needed. To date, experimental tests are limited to single-particle interference exploiting a closed phase relation in a three-path interferometer called the Peres test. The latter distinguishes complex quantum mechanics from quaternionic quantum mechanics. Here, we propose a general matrix formalism putting the Peres test on a solid mathematical ground. On this basis, we introduce multipath and multiparticle interference tests, which provide a direct probe for any dimension of the number system of quantum mechanics.
CRIS-Team Scopus Importer:2025-02-28